Body image dissatisfaction and low self-esteem due to physical appeareance in students of the faculty of medicine at the university of los andes (mérida, venezuela) - López Atencio, Pedro (2008)
The purpose of this investigation was to evaluate body image dissatisfaction in relation to low self-esteem due to physical appearance in students of the Faculty of Medicine at the University of Los Andes in Mérida, Venezuela.  It was a non-experimental and correlational study.  The sample included 189 students (27% male and 73% female) with an average age of 19.58 ± 1.57 (men: 19.81 years of age ± 1.74 and women: 20.24 years of age ± 1.76).  Participants were intentionally selected from first-year courses of the Medicine, Nursing and Nutrition programs.  The Body Shape Questionnaire (BSQ) (Cooper and Taylor, 1987) was the instrument used to measure body image dissatisfaction and Graffar’s modified method (Méndez and De Méndez, 1994) was applied to determine the participants’ socioeconomic status.  A descriptive analysis (frequency, percentages, mean) and an inferential analysis (one-way ANOVA) were applied to the data using SPSS (Statistical Package for Social Sciences) version 9.0.  One of the most important findings in this study was the determination of a statistically significant relationship between dissatisfaction and body image and between low self-esteem and gender χ2 (2, N= 189) = 9.686, p=0.008.  Using ANOVA also helped determine that differences in the mean for dissatisfaction and low self-esteem levels with body image and gender are statistically significant, F= 11.236; p=0.008, F=10.23; p=0.002, respectively.  Conclusions: results obtained suggest a relationship between dissatisfaction and low self-esteem due to physical appearance. Consequently, subjects reject their body image because of a distorted or undistorted perception of their physical appearance, which can possibly affect self-esteem.  Moreover, it is observed that the students’ psychological health is more related to their satisfaction with their body-image than to the way their body image is perceived. Consequently, this group of participants must be analyzed regarding their self-esteem due to body image, as an expression in the institutional environment.  It is also important to emphasize that gender may be a risk factor concerning eating disorders.  We believe the foregoing because women showed higher dissatisfaction levels because of their physical appearance being conditioned by a higher dissatisfaction with their perceived body image, which is characterized by an overestimation of the physical dimension of their body image.